The need for novel strategies to address postoperative pain associated with cardiac surgery: A commentary and introduction to "SMArTVIEW". Issue 2 (15th July 2019) - Ouellette, Carley; Henry, Shaunattonie; Turner, Andy; Clyne, Wendy; Furze, Gill; Bird, Marissa; Sanchez, Karla; Watt-Watson, Judy; Carroll, Sandra; Devereaux, PJ; McGillion, Michael
ABSTRACT: Background : With coronary heart disease affecting over 2.4 million Canadians, annual cardiac and major vascular surgery rates are on the rise. Unrelieved postoperative pain is among the top five causes of hospital readmission following surgery; little is done to address this postoperative complication. Barriers to effective pain assessment and management following cardiac and major vascular surgery have been conceptualized on patient, health care provider, and system levels. Purpose : In this commentary, we review common patient, health care provider, and system-level barriers to effective postoperative pain assessment and management following cardiac and major vascular surgery. We then outline the SMArTVIEW intervention, with particular attention to components designed to optimize postoperative pain assessment and management. Methods : In conceptualizing the SMArTVIEW intervention design, we sought to address a number of these barriers by meeting the following design objectives: (1) orchestrating a structured process for regular postoperative pain assessment and management; (2) ensuring adequate clinician preparation for postoperative pain assessment and management in the context of virtual care; and (3) enfranchising patients to become active self-managers and to work with their health care providers to manage their pain postoperatively. Conclusions : Innovative approaches to address these barriers are a current challenge to health care providers and researchers alike. SMArTVIEW is spearheading this paradigm shift within clinical research to address barriers that impair effective postoperative pain management by actively engaging health care providers and patients in an accessible format (i.e., digital health solution) to give primacy to the need of postoperative pain assessment and management following cardiac and major vascular surgery.